Inter-Genera Colonization of Ocimum tenuiflorum Endophytes in Tomato and Their Complementary Effects on Na+/K+ Balance, Oxidative Stress Regulation, and Root Architecture Under Elevated Soil Salinity - Sahu, Pramod K.; Singh, Shailendra; Singh, Udai B.; Chakdar, Hillol; Sharma, Pawan K.; Sarma, Birinchi K.; Teli, Basavaraj; Bajpai, Raina; Bhowmik, Arpan; Singh, Harsh V.; Saxena, Anil K. (Frontiers in Microbiology, 2021)
Endophytic bacilli of ethano-botanical plant Ocimum tenuiflorum were screened for salt stress alleviating traits in tomato. Four promising O. tenuiflorum endophytes (Bacillus safensis BTL5, Bacillus haynesii GTR8, Bacillus paralicheniformis GTR11, and Bacillus altitudinis GTS16) were used in this study. Confocal scanning laser microscopic studies revealed inter-genera colonization of O. tenuiflorum endophytes in tomato plants giving insights for widening the applicability of potential endophytes to other crops. Further, in a pot trial under 150 mM NaCl concentration, the inoculated endophytes contributed in reducing salt toxicity and improving recovery from salt-induced oxidative stress by different mechanisms. Reduction in reactive oxygen species (sub-cellular H2O2 and superoxide) accumulation was observed besides lowering programmed cell death and increasing chlorophyll content. Endophyte inoculation supplemented plant antioxidant enzyme system via modulation of enzymatic antioxidants viz. peroxidase, ascorbate peroxidase, superoxide dismutase, and catalase apart from increasing proline and total phenolics. The antioxidants like proline have dual roles of antioxidants and osmoregulation which might also have contributed to improved water relation under elevated salinity. Root architecture viz., root length, projection area, surface area, average diameter, tips, forks, crossings, and the number of links were improved upon inoculation indicating healthy root growth, enhanced nutrient flow, and water homeostasis. Regulation of Na+/K+ balance and water homeostasis in the plants were also evident from modulation in expression of abiotic stress-responsive genes viz., LKT1, NHX1, SOS1, LePIP2, SlERF16, and SlWRKY39. Shoot tissues staining with light-excitable Na+ indicator Sodium Green™ Tetra (Tetramethylammonium) Salt showed low sodium transport and accumulation in endophyte inoculated plants. All four endophytes exhibited different mechanisms for stress alleviation and indicated complementary effects on plant growth. Further, this could be harnessed in form of a consortium for salt stress alleviation. The present study established inter-genera colonization of O. tenuiflorum endophytes in tomato and revealed its potential in maintaining Na+/K+ balance, reducing reactive oxygen species, and improving root architecture under elevated salinity.